2005
DOI: 10.1111/j.1460-2695.2005.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue resistance of CrN thin films deposited by arc evaporation process on H11 tool steel and 2205 duplex stainless steel

Abstract: A B S T R A C T Notwithstanding the wide use of PVD coated components, not only in fields where tribological behaviour is important and well assessed, fatigue behaviour is still an object of research in applications where enhanced fatigue resistance is required. The aim of this paper is to analyse fatigue crack growth mechanisms and to relate their nucleation sites to the microstructure and to residual stress data. Two structural steels were used as the substrate (H11 tool steel grade and 2205 duplex stainless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Several published data on single and multilayer PVD coatings consider the effects of the interface adhesion, of the residual stress distribution, and of the type of the microstructure that strongly influences the mechanical behavior of the substrate/coating system [11][12][13]. However, only few studies correlated coating performances with the substrate mechanical properties [14] and the coating defects in terms of wear behavior and corrosion resistance.…”
Section: Introductionmentioning
confidence: 96%
“…Several published data on single and multilayer PVD coatings consider the effects of the interface adhesion, of the residual stress distribution, and of the type of the microstructure that strongly influences the mechanical behavior of the substrate/coating system [11][12][13]. However, only few studies correlated coating performances with the substrate mechanical properties [14] and the coating defects in terms of wear behavior and corrosion resistance.…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, a study on CrN deposited on steel demonstrates that the fatigue resistance is enhanced after the mechanical surface treatment, due to the increase in the residual compressive stress of the substrate skin [13]. As known, in fact, the fatigue cracks in PVD coated parts nucleate at the interface between coating and substrate [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…If the deposited layer is free from defects, and does not delaminate, these compressive stresses are expected to improve fatigue life [33][34][35][36][37][38][39]. However, it has been observed that the deposition of a coating reduces the strength of aluminum components [40] while has little effect on the fatigue resistance of steel components [41,42].…”
Section: Introductionmentioning
confidence: 99%